The photoresponse properties of nanostructured Cu:CdO thin film based photodiodes - Soylu, M.; Dere, A.; Yakuphanoğlu, Fahrettin (Academic Press Ltd- Elsevier Science Ltd, 2025)
CdO and Cu doped CdO (Cu:CdO) were coated by a spin coating technique on glass and p-Si substrates. Optical characterization was conducted for the thin films synthesized on the glass substrates. The current-voltage (I-V) measurements of Al/Cu:CdO/p-Si heterojunctions with undoped, 1 %, 3 %, 5 % and 10 % Cu doped CdO were performed in dark and under various illumination intensities. The I-V curves revealed that the Al/Cu:CdO/p-Si structure showed the photodiode behaviour. It was seen that the photosensitivity (PS) and detectivity (D) became more efficient with the excess Cu doping. While the capacitance-voltage (C-V) and photocapacitance varied depending on the Cu wt.% content, the diode with undoped CdO layer exhibited the highest capacitance. The transient photocurrent (I-t) and transient photocapacitance (C-t) measurements were carried out for time-resolved observation. The interface state density (Dit) varied with the Cu wt.% content in the CdO. It was seen that the optimized diode parameters of the Al/Cu:CdO/p-Si contacts could be specified by suitably choosing the Cu wt.% content. This work presents an occasion to develop the optoelectronic devices based on Cu doped CdO thin films.
Keywords: CdO thin films; Doping Cu; Heterojunction; Photoresponse